Coupled enhancer and coding sequence evolution of a homeobox gene shaped leaf diversity - Vuolo, F; Mentink, R; Hajheidari, M; Bailey, C; Filatov, D; Tsiantis, M (Cold Spring Harbor Laboratory Press, 2016)
Here we investigate mechanisms underlying the diversification of biological forms using crucifer leaf shape as an example. We show that evolution of an enhancer element in the homeobox gene REDUCED COMPLEXITY (RCO) altered leaf shape by changing gene expression from the distal leaf blade to its base. A single amino acid substitution evolved together with this regulatory change, which reduced RCO protein stability, preventing pleiotropic effects caused by its altered gene expression. We detected hallmarks of positive selection in these evolved regulatory and coding sequence variants and showed that modulating RCO activity can improve plant physiological performance. Therefore, interplay between enhancer and coding sequence evolution created a potentially adaptive path for morphological evolution.